Impact of Different Shade levels on Growth and Yield Performance of Different Varieties of Bellpepper (Capsicum annuum L.). - Thushari, S.E.E.M.; Pradheeban, L.; Nishanthan, K. (University of Jaffna, 2020)
Bell pepper (Capsicum annuum L.) is an important Solanaceous family vegetable in the world, but commercial cultivation are limited in Sri Lanka. An experiment was conducted to access the effect of different shade levels on the growth and yield of bell pepper (Capsicum annuum L.) at Department ofAgronomy, Faculty of Agriculture, Ariviyal Nagar, Kilinochchi during March to July in 2018. Two factor factorial experiment was carried out in Complete Randomized Design (CRD) with six replicates. Four shade levels (25%, 50%, 75%and 85%shade levels) and three varieties; Yellow (Polaris), Green (Ganga) and Red (Hercules) were used as treatments. Weather, growth and yield parameters were recorded and data were analyzed in ANOVA using SAS 9.1 package. The means were compared by using Duncan Multiple Range test. All other management practices were performed based on the farmer practices adopted in BadullaDistrict. Light intensitywas significantly differed among shade levels and the lowest in the85%shade level and highest in the25%shade and the temperature and relative humidity were not much varied among the shade levels. There was a significance difference in vegetative growth traits (plant height, number of leaves and branches per plant) and yield parameters (fruit length, fruit diameter, fruit weight, number of fruits per plant and yield) of bell pepper among shade levels and varieties. In the growth parameters, the plant height was highest in 85% shade level in yellow variety and other parameters of growth were highest in 25% shade level in green variety. In the yield parameters, the number of fruit was highest in 25% shade level in red variety and other yield parameters such as fruit length, fruit diameter and fruit weight were highest in 85% shade level in yellow variety. It can be concluded that 85% shade level and yellow variety can be recommended as the best combination for growing of bell pepper in Kilinochchi District during Yala season based on the growth and yield performance of the plant.
Keywords: Bell pepper.; Shade level; Varieties.; Vegetative growth traits; Yield parameters